Uma ferramenta para projeto de sistemas de diálogos para call center baseados em asterisk - BORGES FILHO, Estillac Lins Maciel (Universidade Federal do Pará, 2014)
This work presents DialogBuilder, an open-source Java tool that provides to its user an interface for designing dialog systems and exporting them to code that can be deployed in Asterisk, the most popular VoIP framework. DialogBuilder offers to the novice users a wizard so that they can design their own dialog system without learning the intricacies of programming for Asterisk. The software separates the stages of dialog conception and its programming and is positioned to make technically and economically viable, even for small businesses, to construct and maintain dialog systems for telephony applications.